School Leadership Practices and Identity Politics in a Multicultural Society: The Case of Indonesia - Raihani Raihani (Journal of Asian Social Science Research, 2022)
This article aims to explore school leadership practices in the context of the multicultural society of Indonesia. Effective school leaders in a diverse context demonstrate a type of moral leadership characterized by high awareness and sensitivity to cultural diversity and act accordingly to enable everyone in school to pursue his or her goals. This study used a qualitative case study approach by selecting three different schools and interviewing the principals, teachers, and students. The findings suggest that while in rhetoric school leaders convey a commitment to recognize and respect diversity, they exercise covertly some discriminative policies towards powerless groups. In these schools, both cultural and religious identities were used to maintain domination in school. Consequently, the schools have hardly become a venue for social justice and multicultural citizenship. By doing so, this article contributes to a better understanding of the nuance of school leadership in multicultural societies like Indonesia.